The Effect of Audit Quality and Auditor's Opinion on Earnings Management: Evidence from Jordan - Sharf, Noor; Abu Nassar, Mohammad (Jordan Journal of Business Administration, 2021)
This study examines the effect of audit process quality and auditor's opinion on earnings management in industrial companies listed in Amman Stock Exchange (ASE) in Jordan, during the period from 2006 to 2015. Three measurements were used to indicate the effect of audit process quality on earnings management (tenure, audit firm size and auditor specialization). The final sample included 57 industrial companies listed in ASE with 547 observations. This study utilized panel secondary data derived from financial statements. Correlations and multiple regression analysis were used to test the effect of audit process quality and auditor's opinion on earnings management.The results revealed that tenure has a statistically negative relation with earnings management. In addition, auditor specialization measured by client firm size plays a critical role in reducing earnings management. On the other hand, an insignificant effect of audit firm size on earnings management is observed. Furthermore, the results showed that when we move from unqualified opinion to disclaimer opinion, the extent of earnings management increases.Based on these results, it is recommended to reconsider mandatory audit firm rotation by regulators and standards’ setters.